Ex vivo tracking of endogenous CO with a ruthenium(II) complex - de,la Torre C; Toscani,A; Marin-Hernandez,C; Robson,J; Terencio,M; White,A; Alcaraz,M; Wilton-Ely,JD; Martinez-Manez,R; Sancenon,F (Journal of the American Chemical Society, 2017)
A two-photon fluorescent probe based on a ruthenium(II) vinyl complex is capable of selectively detecting carbon monoxide in cells and ex vivo using mice with a subcutaneous air pouch as a model for inflammation. This probe combines highly selective and sensitive ex vivo detection of endogenous CO in a realistic model with facile, inexpensive synthesis, and displays many advantages over the widely used palladium-based systems.